HIGHER EDUCATION PRIESSIONAL FEMININE DEFICITS IN HEALTH SCIENCES IN NIGERIA - Mowaiye Fagbemi O; Aderinto S; Yenizzar Yenizzar (Universitas Bina Bangsa Getsempena, 2025)
There are important psychological processes involved in career socialization and specialization. Such processes streams line many into specialised profession and areas of study thereby entrenching a gendered structure of specialization in any gendered society. Nigeria is a developing nation and still trying to over come gender limiting norms ,one of which is assigned masculine and feminine attributes to some fields and professions, one of which is the health sector . With such a background, the paper attempted to delve into the ratio of males and females within the Nigerians University system in the health sciences using the case study model. The paper revealed a paucity of females in the sector and made recommendations for improvement given the critical nature of the sector and the spate of development in the sector in the global village which Nigeria aims to join in development.